Tumor-associated macrophage-derived exosome miR-194 confers cisplatin resistance in GC cells - Yi Zhou; Yang-cheng Sun; Qiong-yan Zhang; Jing Wang; Xian-ya Zhu; Xiang-yu Su (European Journal of Medical Research)
Abstract Objective At all stages of gastric cancer (GC), cisplatin is the first-line chemotherapeutic agent, but its efficacy remains limited, with a response rate of less than 20%, largely because of resistance to the drug. It aims to determine whether macrophage-derived exosomes are involved in the mechanism of cisplatin resistance, in order to identify potential methods for reversing resistance and improving patient outcomes. Methods Macrophages induced by IL-13 and IL-4 were characterized using flow cytometry, then co-cultured with GC cells and cisplatin. Cell viability and apoptosis were subsequently evaluated through CCK-8 assays and flow cytometry. Exosome miR-194, derived from M2 macrophages, was characterized and co-cultured with gastric cancer cells and cisplatin to assess cell survival. Furthermore, a mouse GC model was established, and miR-194 was injected to observe tumor growth. Results Results indicate that M2 macrophages enhance cisplatin resistance in gastric cancer cells mainly through miR-194, as demonstrated by CCK-8 and apoptosis assays. Cellular uptake experiments demonstrated that miR-194 can transfer from macrophages to GC cells and exert functional effects. Western blotting and PCR analysis further confirmed that macrophage-derived miR-194 inhibits apoptosis in GC cells and enhances cisplatin resistance by downregulating PTEN. Conclusion Macrophage-derived miR-194 promotes cisplatin resistance in GC cells by inhibiting apoptosis through PTEN downregulation. These findings provide new insights and theoretical backing for clinical treatment strategies in GC.